Tooth Wear Lesions: Prevalence and Associated Risk Factors Among Patients Attending the Dental Clinic of a Tertiary Hospital in Ondo State, Nigeria (Nigerian Dental Journal, 2025)
ObjectiveTo determine the prevalence of tooth wear lesions and assess associated risk factors among patients attending the dental clinic of a state tertiary teaching hospital in Nigeria.BackgroundThis cross-sectional study was conducted over a three-month period among randomly selected patients attending the outpatient dental clinic of the University of Medical Sciences Teaching Hospital. Data were collected using a structured questionnaire to obtain socio-demographic information, lifestyle factors, oral habits, and oral hygiene practices potentially associated with tooth wear. Clinical examination for tooth wear was performed using the Smith and Knight Tooth Wear Index. Data were analyzed using SPSS version 25, with statistical significance set at p < 0.05.ResultsA total of 102 participants aged 16 years and above were included, comprising 55 males (53.9%) and 47 females (46.1%). The overall prevalence of tooth wear was 56.9%. Among the 9,792 examined surfaces, 61.3% showed signs of wear, while 36.9% of participants exhibited pathological wear. Erosion was the most prevalent type (28.5%), followed by attrition (15.8%) and abrasion (12.4%). Multiple lesion types were observed in 8.8% of participants. Males had more worn surfaces (56.6%) than females (43.4%), though the difference was not statistically significant (p = 0.928). Tooth wear was significantly associated with age (p < 0.01), with the highest prevalence in individuals aged 40–49 years (18.7%) and those aged 50 and above (20.8%). Pathological wear was also most common in these age groups. Nail biting showed a strong association with tooth wear (p < 0.01), while bruxism demonstrated borderline significance (p = 0.05). Dietary factors, including daily consumption of fruit juice (p = 0.015) and soft or energy drinks (p = 0.021), were significantly associated with tooth wear, highlighting dietary acids as key contributors.ConclusionTooth wear is highly prevalent, particularly among adults over 40 years of age, with erosion being the most common type. Age, nail biting, and frequent fruit juice consumption were the most significant predictors. These findings emphasize the need for early risk assessment, patient education, and behavioural interventions to prevent the progression and long-term effects of tooth wear.
Keywords: Risk factor; Attrition; Abrasion; Erosion; Toothwear lesion